(untitled) (Vietnam Journal of Community Medicine, 2024)
Background: To help managers have a basis to improve environmental sanitation conditions for ethnic people in general and the Dao ethnic group in particular. Objective: Describe the current situation and some factors related to the management and protection of the ecological environment of the Dao people in Kim Boi District, Hoa Binh Province in 2021. Research subjects and methods: Cross-sectional descriptive research, quantitative combined with qualitative research conducted on 603 Dao households living in the Kim Boi district from January 2021 to October 2021. Results and conclusions: The proportion of Dao people who have satisfactory behavior on environmental sanitation, but is low, is as follows: 39.6% have satisfactory behavior on using hygienic water sources; 24.7% of behaviors achieved human excrement management; 14.1% on quality classification; 26.6% on waste treatment. Some factors related to environmental sanitation behavior are Household economy, physical hygiene, education level, and knowledge and attitudes of the Dao people about sanitation. Building a communication model to change environmental sanitation actions for Dao people in Hung Son commune.